Rancangan Praksis Pendidikan Kristen Berbasis Keluarga Beriman dari Generasi ke Generasi - Lie, Tan Giok (Veritas : Jurnal Teologi dan Pelayanan, 2019)
Designing a Praxis of Christian Education Based on Family of Believers from Generation to Generation. Facts in almost every branch of science, including practical theology in the field of Christian education, show that there is a gap between theory and practice as if the practice cannot be carried out according to its theory, even though theory serves as a foundation for building practice. Therefore, theory and practice must be integrated into a single unit called praxis. The praxis will be effective because it is clear in its purpose, essence, scope, and strategy. This is a crucial thing that needs to be done by Christian educators. However, designing a praxis is not an easy matter. In response to this, the author presents a praxis draft of Christian education built on theological and historical studies of the theology of covenant in the light of Christian education of faith-based families and is equipped with practical recommendations for the preservation of God's covenant from generation to generation. It is hoped that this praxis design will encourage every practitioner of Christian education to build personal praxis.